Multilevel Authentication in Smart Online Classroom Attendance - Kamarudin N.H.; Siong J.J.; Solihin M.I.; Hayder G. (Springer Nature, 2024)
This project presents a prototype of a multilevel authentication in smart online classroom attendance. The scope of this project includes some steps. It begins with conceptual design of a multilevel authentication for students attendance in the online classroom application. The system generates a student unique identity for the first-level authentication followed by a biometric authentication for student verification. Overall, the development of a multilevel authentication scheme for the online classroom is presented in this paper. The prototype can authenticate the student unique identity and biometric authentication for student verification. In addition, the designed smart system prototype is also able to store the student attendance and sending back to the lecturer. 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.